A finite difference technique for solving incompressible fluid flow and energy equations on distributed parallel computer system - Manshoor, Bukhari; Wan Hassan, Mat Nawi; Alias, Norma (2006)
This paper is concemed with the development of an efficient for solving the finite difference Navier-Stokes and energy equations using distributed parallel computer system. The numerical procedure is based on SIMPLE (Semi Implicit Method Pressure Link Equations) developed by Spalding.